India : Orissa State Financial Accountability Assessment - World Bank (Washington, DC, 2013)
The Country Assistance Strategy for India places emphasis on the need for modernizing public financial management, and accountability systems, and, undertaking such diagnostic work as necessary to help build Government's capacity for better public sector management, and external scrutiny. It calls for financial accountability assessments to be carried out in all States where programmatic adjustment loans are being prepared, supporting reforms associated with fiscal, and fiduciary risks management. Of India's 14 major States, Orissa has the second lowest, per capita income, and a growth rate of 3 percent against the national average of 5-6 percent per annum, while statistics also show its revenue, and fiscal deficits increased significantly over the years. The Government of Orissa is developing a robust reform program, reforms which on the fiscal side, are fully consistent with recommendations for strengthening financial management, and public accountability, as proposed in this State Financial Accountability Assessment (SFAA) Report. This SFAA is designed to ascertain and help mitigate the extent to which public firms in Orissa State, are exposed to fiduciary risks, and it further points to the need for capacity building, in almost every significant aspect of public financial accountability. It is reported that while the legal/regulatory/institutional frameworks for internal control, and internal audit compares favorably with the rest of India, it does less so with international best practice, and, although accounting and financial reporting rules comply with well-established national requirements, it does not with International Public Sector Accounting Standards (IPSAS) for cash based accounting, and financial reporting. Recommendations suggest to encourage the enlargement of the role of the State Accountant General - AG - (Audit) in following up cases of previous Audit Reports which the Committees may not like to pursue for detailed examination; to discuss the most recent reports of the Controller and Auditor General (CAG) as a matter of priority; to include in the annual confidential reports of the departmental officers, an assessment of the quality of response to the audit reports, and recommendations of the Committees; and, civil society should be sensitized, and involved in the accountability process, to achieve transparency.